(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
The Messinian-Zanclean boundary in the Mediterranean basin marks the end of the Messinian salinity crisis (MSC) at approximately 5.33 Ma. The mechanism behind the return to normal marine conditions after the MSC are debated, with two main hypotheses proposed: an instantaneous reflooding of the Mediterranean at the base of the Zanclean, following its near-complete desiccation, or a gradual sea level rise in a non-desiccated basin during the late MSC phase (Lago-Mare). Our objectives are to refine the age model of the Pollenzo section in the Piedmont basin, Italy, and to elucidate environmental variability during this phase. We employ high-resolution biomagnetostratigraphic and cyclostratigraphic analyses, integrated with statistical multivariate and cluster analyses, and tie the results with other Italian Mediterranean reference sections of the basal Zanclean. The proposed age model is based on biostratigraphic markers (planktic foraminifera and calcareous nannofossils), alongside the identification of the base of the Thvera subchron. Although no astrochronological tuning was proposed, the influence of orbital parameters variation on calcareous plankton was noted, especially at tie of eccentricity maxima. Our results indicate a gradual restoration of open marine conditions after the MSC, spanning from 5.33 to 5.23 Ma. We observe a transition from a more marginal environment to more open marine conditions at the termination of MSC. Our findings challenge the notion of an abrupt transition at the end of the MSC, emphasizing the gradual nature of environmental change in the northernmost Mediterranean basin, from the late Messinian to the early Zanclean.